Anatomical functional traits and hydraulic vulnerability of trees in different water conditions in southern Amazonia. Issue 4 (10th April 2023) - Ribeiro‐Júnior, Norberto G.; Marimon, Ben Hur; Marimon, Beatriz S.; Cruz, Wesley J. A.; Silva, Ivone V.; Galbraith, David R.; Gloor, Emanuel; Phillips, Oliver L.
Abstract: Premise: Understanding tree species' responses to drought is critical for predicting the future of tropical forests, especially in regions where the climate is changing rapidly. Methods: We compared anatomical and functional traits of the dominant tree species of two tropical forests in southern Amazonia, one on deep, well‐drained soils (cerradão [CD]) and one in a riparian environment (gallery forest [GF]), to examine potential anatomical indicators of resistance or vulnerability to drought. Results: Leaves of CD species generally had a thicker cuticle, upper epidermis, and mesophyll than those of GF species, traits that are indicative of adaptation to water deficit. In the GF, the theoretical hydraulic conductivity of the stems was significantly higher, indicating lower investment in drought resistance. The anatomical functional traits of CD species indicate a greater potential for surviving water restriction compared to the GF. Even so, it is possible that CD species could also be affected by extreme climate changes due to the more water‐limited environment. Conclusions: In addition to the marked anatomical and functional differences between these phytophysiognomies, tree diversity within each is associated with a large range of hydraulic morphofunctional niches. Our results suggest the strong potential for floristic and functional compositional shifts under continued climate change, especially in the GF. Abstract : The variety of structural characteristics of tree leaf and stem tissues indicate vulnerability to extreme climatic variations.